In Vitro Antioxidant Properties and Methylglyoxal (MGO) Scavenging Effects of Centella asiatica Leaves in Water Extract - Chong, Xiu Qing; Li, Ann Saw; Jia, Ying Puah; AP Anamalay, Kirthani; Patrick, Nwabueze Okechukwu; Hor, Kuan Chan (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: Advanced glycation end product (AGE) is formed by the non-enzymatic glycation, leading to free radicals’ production and high oxidative stress. Accumulation of AGEs is associated with chronic diseases which are correlated with diabetes mellitus. Centella asiatica is a traditional medicinal herb used in Asia with numerous pharmacological effects such as antioxidant, wound healing, neuroprotective, and gastrointestinal treatment. This research was aim to evaluate the antioxidant, antiglycation, and phytochemical analysis of C. asiatica leaves (L.) water extract. Methods: The antioxidant activity of the plant extract was evaluated through 2,2-diphenyl-1-picrylhydrazyl (DPPH), hydroxyl (OH) radicals, nitric oxide (NO), and chelating capacity assays. Total phenolic content (TPC) was performed to determine the presence of bioactive compounds, such as saponins, which have been extensively reported in previous studies. Butylated hydroxytoluene (BHT) and ethylenediaminetetraacetic acid (EDTA) were used as positive control in the antioxidant assays, while quercetin was used in the antiglycation assays. Antiglycation effects of C. asiatica L. were evaluated through Bovine serum albumin (BSA)-MGO, BSA-glucose, and MGO scavenging assay. The data was expressed in terms of IC50. Result: The plant extract possessed significantly (p < 0.001) lower IC50 value compared to the BHT in DPPH and NO radical scavenging assay. It also showed stronger antiglycative effect with lower IC50 value compared to the quercetin in BSA-glucose and BSA-MGO assay. The TPC of C. asiatica L. was 3.20 mg/GAE/g at 100μg/ml. Conclusion: The antiglycation effects of C. asiaitca L. include the reduction of Amadori products formation, trapping α-dicarbonyl intermediates, and free radical scavenging. It is suggested that the antiglycation effects of C. asiatica L. maybe attributed by the presence of saponins and other phytochemicals.